Syntheses, crystal structures and catalytic property of two bulky tin(II) complexes. (15th November 2020) - Yu, Dehui; Tong, Hongbo; Zhou, Meisu
Graphical abstract: Two bulky tin(II) complexes 1 and 2 have been prepared. Their single-crystal structures and catalytic behaviors are presented. Highlights: Two bulky three-coordinate tin(II) complexes 1 and 2 were synthesized. Their single-crystal structures were presented. Complex 1 showed good catalytic activity in catalytic addition of aniline to carbodiimide. Abstract: Two bulky three-coordinate tin(II) complexes 1 and 2 have been prepared: [N(Ar)C(R)NC(R)N(R′)]SnCl (Ar = 2, 6- i Pr2 C6 H3, R = NMe2, R′ = H, 1 ; R = 1-piperidino, R′ = SiMe3, 2 ). Their single-crystal X-ray diffraction studies are presented. They can be used as efficient pre-catalysts for catalytic addition of arylamines to N, N' -diisopropylcarbodiimide.